How Italian nurses perceive nursing leadership twenty years after its establishment: an historical observational perception study - Vitale, Elsa; Galatola, Vito (Medicina Historica, 2022)
The nursing manager role and the function that he has in health organizations is a topic that has become increasingly important in recent years. The purpose of this study is to evaluate the impact and perception of nursing management on nursing staff investigating: human resource, development and training, human resource management, work organization leadership, and listening. The research was conducted through questionnaires administered online through social networks as Facebook and Instagram. A total of 739 nurses participated in the study. The data collected show a very low level of perception of the figure of the nursing manager and very often this perception does not differ considering the two groups of interviewees. About twenty years after his birth, the “distance” between nurses and nursing management still exists.